Significance of the imidazoline receptors in toxicology - Lowry, J. A.; Brown, J. T. (Clinical toxicology (Philadelphia, Pa.), 2014)
Abstract Introduction. The alpha-2 adrenergic (AA-2) receptor agonists and imidazolines are common exposures in the American Association of Poison Control Centers (AAPCC) National Poison Data System (NPDS). Although the interaction between the AA-2 receptor and imidazoline receptors has been extensively studied, it largely remains unknown to health-care professionals. This review describes these interactions and mechanisms by which agonists affect physiologic responses binding to these receptors. Methods. Papers published in English from 1960 to 2013 were retrieved from PubMed. A total of 323 original articles were identified and 173 were included. Background. The toxicity associated with clonidine (e.g., bradycardia, miosis, and hypotension) is largely assumed to be secondary to the functional overlap of the AA-2 receptors and the mu receptors. However, the effects at the AA-2 receptor could not fully account for these symptoms. Subsequently, clonidine was found to produce its pharmacologic effect in the central nervous system (CNS) by interaction not only with the AA-2 receptor but also on selective imidazoline receptors. Imidazoline receptors. Since their discovery, three distinct classes of imidazoline receptors, also known as imidazoline binding sites or imidazoline/guanidinium receptive sites, have been characterized. Imidazoline-1 (I-1) receptors are involved in the hypotensive activity of clonidine and related compounds supporting the idea that the I-1 receptors are upstream from the AA-2 receptor and work in tandem for its effect on blood pressure. Additionally, stimulation of N-type Calcium-2 channels, G-protein inwardly rectifying potassium channel, adenosine receptors, phosphatidyl-choline-specific phospholipase C, and nicotinic receptors have been implicated to be involved. Previous studies have shown that I-1 receptors may also be involved in other physiologic responses beyond cardiac function. Imidazoline-2 (I-2) receptors interact with monoamine oxidase A and monoamine oxidase B leading to research that has focused on the effect of I-2 receptors and depression and the suggestion of a possible antidepressant action of the imidazolines. I-2 receptor ligands may have substantial antinociceptive activity and work synergistically with opioids in acute pain. Imidazoline-3 (I-3) receptors are located on the pancreatic β-cells and modulate glucose homeostasis. Imidazoline ligands. Four endogenous compounds have been found to bind and include clonidine-displacing substance, agmatine, harmane, and imidazole acetic acid. Significant interest in developing new agents with higher selectivity and affinity for I-1 receptors has resulted. Toxicology. Alpha-2 adrenoceptor and imidazoline receptor agonists such as clonidine and tetrahydrozoline are common ingestions reported to poison control centers. The most common toxic effects of clonidine are similar to those of the over-the-counter imidazolines and include CNS depression, bradycardia, hypotension, respiratory depression, miosis, hypothermia, and hypertension (early and transient). Based on their structure and subsequent studies, imidazoline receptors seem to be the primary binding site for these chemicals. Case reports typically illustrate rapid onset of action with serious side effects following ingestion of relatively small amounts. These agents have been reportedly used in drug-assisted sexual assaults. Conclusion. Much of the toxicity associated with drugs such as clonidine, guanfacine, and tetrahydrozoline are due to their binding to imidazoline receptors. Knowledge of the imidazoline receptors may lead to new therapeutic agents and inform management of patients with imidazoline overdose.